Covid-19 World Order and Global Solidarity: The African Continents Pains and Gains - Adebajo, Adeola Aderayo; Ayodeji, Gafar Idowu; Olayinka, Iseoluwa Raphael; Obafemi, Akintomiwa Olaniyi (Kashere Journal of Politics and International Relations, 2025)
The paper investigates how paradigm shifts caused by varying interests, actions, or inactions of global actors and nationals during the COVID-19 Pandemic undermine the international community's ability to band together to mitigate the devastating effects of the COVID-19 Pandemic. The study maintained that the world is gradually transiting into the epoch of multiplex world order where the paramount major powers lack the capacity to shape the world order to favour their own interests, among other competing great powers, regional giants, and emerging powers. In light of this, Africa was regarded as one of the most vulnerable continents adversely affected by the pandemic. Therefore, the study seeks to ascertain the extent to which it affects the African continent by weighing the cost and the benefit of the pandemic. In conclusion, the study recommended a homegrown solution against future reoccurrence.